Extending the Sensitivity of CEST NMR Spectroscopy to Micro‐to‐Millisecond Dynamics in Nucleic Acids Using High‐Power Radio‐Frequency Fields. Issue 28 (11th May 2020) - Rangadurai, Atul; Shi, Honglue; Al‐Hashimi, Hashim M.
Abstract: Biomolecules undergo motions on the micro‐to‐millisecond timescale to adopt low‐populated transient states that play important roles in folding, recognition, and catalysis. NMR techniques, such as Carr–Purcell–Meiboom–Gill (CPMG), chemical exchange saturation transfer (CEST), and R 1ρ are the most commonly used methods for characterizing such transitions at atomic resolution under solution conditions. CPMG and CEST are most effective at characterizing motions on the millisecond timescale. While some implementations of the R 1ρ experiment are more broadly sensitive to motions on the micro‐to‐millisecond timescale, they entail the use of selective irradiation schemes and inefficient 1D data acquisition methods. Herein, we show that high‐power radio‐frequency fields can be used in CEST experiments to extend the sensitivity to faster motions on the micro‐to‐millisecond timescale. Given the ease of implementing high‐power fields in CEST, this should make it easier to characterize micro‐to‐millisecond dynamics in biomolecules. Abstract : I′ve got the power : High‐power radio‐frequency fields extend the sensitivity of chemical exchange saturation transfer (CEST) NMR spectroscopy to enable the detection of conformational exchange on the micro‐to‐millisecond timescale. This is applied to the detection of nucleic‐acid dynamics.